AB0312 REAL-LIFE DATA ON THE USE OF BIOLOGICAL DMARDS IN RHEUMATOID ARTHRITIS IN AUSTRIA WITH SPECIAL ATTENTION TO SWITCHING AFTER FIRST BDMARD FAILURE. (2nd June 2020) - Nell-Duxneuner, V.; Reichardt, B.; Stamm, T.
Abstract : Background: The introduction of biological disease modifying anti-rheumatic drugs (bDMARDs) offered new dimensions in controlling disease progress for patients with Rheumatoid Arthritis (RA). According to the recommendations by EULAR, treatment should be commenced with a conventional synthetic DMARD as soon as diagnosis is made, followed by a bDMARD after treatment failure. The choice of drug is done in respect to comorbidities, preference of the patient and to costs. Objectives: Drug expenditure data of 2012-2016 were retrieved to evaluate frequency of prescription and drug survival with special focus on switching habits after first bDMARD failure. Methods: Data were extracted from 11 Austrian social health insurance funds covering 86% of the Austrian population. Only patients with first prescriptions of bDMARDs were included. Absolute and relative frequencies of first bDMARD prescriptions, second and third courses of bDMARDs (switches) and probabilities of drug survival of first line bDMARDs were calculated. Baselines were set individually at the beginning of the first bDMARD course. A Sankey diagram was used to illustrate the relationships between first, second and third courses of bDMARDs (Figure). The first left column represents the first bDMARDs, the second and third columns the second and third switched bDMARDs, respectively. The quantity of the bDMARDs is reflected in the width of the lines. Results: 7637 RA patients on bDMARD therapy were retrieved in total. With a presumed prevalence of 0.5% (Ref) this would account for 27% of RA patients being treated with a bDMARD. Of these, 3813 were first time prescriptions. The most commonly prescribed drug in bDMARD naïve patients was Etanercept with 26%, followed by Adalimumab with 25%. Third was Tocilizumab followed by Golimumab (16% and 15%), Abatacept with 9% and Certolizumab and Infliximab with both 4%. Tocilizumab showed the longest drug survival with 80% after one and 61% of patients still on the drug after 3 years. Golimumab was clearly favorable among TNF inhibitors with a drug survival of 71% after one and 50% after 3 years compared to Certolizumab showing the lowest with 63% after one year and only 38% after three years. Tocilizumab was the drug most often switched to after first course failure, followed by Adalimumab. The choice of second bDMARD was different: After Adalimumab failure more patients were switched to another mode of action (almost 50%), predominately Tocilizumab. This is also seen after Golimumab failure and is less pronounced in the other TNF inhibitors: they were mostly switched to second TNF inhibitor, mainly Adalimumab. The majority of patients started on Tocilizumab and Abatacept were switched to a TNF inhibitor (74% and 58%, respectively). In third DMARD choice again Tocilizumab is mostly chosen followed by Abatacept, leaving 42% to a TNF inhibitor, mostly Golimumab. Conclusion: Patients were most often started on a TNF inhibitor as first bDMARD, namely Etanercept and Adalimumab. Golimumab was prescribed less often but showed the longest drug survival among TNF inhibitors. Tocilizumab showed the longest drug survival overall and was the bDMARD most often switched to as second bDMARD. When starting with Adalimumab or Golimumab there was a tendency towards change of mode of action, which was not as pronounced for the other three TNF inhibitors. After failing twice Tocilizumab and Abatacept were the most often prescribed drugs. References: [1]Kobelt G, Fasteng F: Access to Innovative Treatments in Rheumatoid Arthritis in Europe. A Report prepared for the EFPIA, 2009 Acknowledgments: Austrian Main Social Health Association (Dachverband österreichische Sozialversciherung) Disclosure of Interests: Valerie Nell-Duxneuner Speakers bureau: MSD, Pfizer, Jansen, Abbvie, Lilly, Novartis, Berthold Reichardt: None declared, Tanja Stamm Grant/research support from: AbbVie, Roche, Consultant of: AbbVie, Sanofi Genzyme, Speakers bureau: AbbVie, Roche, Sanofi